UPAYA PENYELAMATAN ARSIP KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SLEMAN - Nafiah, Daimatun (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
This study aims to describe efforts in the preservation of population registry information through digitalization processes at Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sleman. The research design employed is a descriptive qualitative research, utilizing a case study approach. Data collection techniques include observation, interviews, and documentary studies. Data analysis follows Miles and Huberman's model, involving data reduction, data display, and conclusion. The findings of this study conclude that: (1) the digitalization process of population registry archives conducted by Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sleman utilizes an application named SIDAR (Information System for Archive Documentation), which involves preparing archives, scanning using scanners, image editing such as image cropping, and storing them in SIDAR application; (2) the implementation of the digitalization process for population registry archives is beneficial for securing, preserving, and conserving both the physical and informational content of the archives, thereby ensuring their usability for the future; (3) challenges in implementing the digitalization process of population registry archives include limited human resources as technical personnel for digitalization, inadequate facilities and infrastructure, and threats from viruses on data storage devices.Keyword: digitalization; archives; information preservation; Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sleman